2013
DOI: 10.2478/s11536-012-0126-5
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic multipartite patella: imaging findings and pain relief. A description of two cases

Abstract: AbstractMusculoskeletal injuries in the non-elite athletes are a clinical entity that is being seen more frequently nowadays. The term “weekend warriors” applies to amateur participants in sports activities and is related to an increasing number of musculoskeletal injuries mainly due to overuse. Concomitant skeletal variations may as well predispose to trauma. We add to the literature two cases of multipartite patella in which locally injected ropivacaine (ropivacaine hydrochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Of the 130 total knees, five studies with 13 knees reported specific return to activity outcomes after conservative management exclusively (10%) [3,22,25,27,30]. These interventions included low-intensity pulsed ultrasound for 20 min a day, immobilization in a plaster cast for three weeks, local injection of ropivacaine hydrochloride betamethasone acetate-betamethasone sodium phosphate targeted at the superolateral pole with weight bearing restriction for three weeks, restriction of activity, and quadriceps strengthening program ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 130 total knees, five studies with 13 knees reported specific return to activity outcomes after conservative management exclusively (10%) [3,22,25,27,30]. These interventions included low-intensity pulsed ultrasound for 20 min a day, immobilization in a plaster cast for three weeks, local injection of ropivacaine hydrochloride betamethasone acetate-betamethasone sodium phosphate targeted at the superolateral pole with weight bearing restriction for three weeks, restriction of activity, and quadriceps strengthening program ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the report by Wong, restriction of activities and a quadriceps strengthening program was enough to get the patient back to playing catcher, although he did continue to have mild pain while in a full squat [30]. Perdikakis and Pthitakis locally injected ropivacaine and a steroid targeted at the fragment into two patients, with one returning to sports but with transient pain with activity and the other remaining pain free but choosing not to return to athletics [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bipartite patella was first described by Gruber [ 5 ] in 1883 and later classified by Saupe [ 6 ] in 1921 into three subgroups based on the location of the fragments. The Saupe classification was reviewed in 2010 by Oohashi et al [ 7 ], who reported more cases of, and presented a new classification of multipartite patella [ 8 ]. Multipartite patella anomaly has been reported as a cause of anterior knee pain and symptomatology [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Saupe classification was reviewed in 2010 by Oohashi et al [ 7 ], who reported more cases of, and presented a new classification of multipartite patella [ 8 ]. Multipartite patella anomaly has been reported as a cause of anterior knee pain and symptomatology [ 8 , 9 ]. In addition, knowledge of multipartite patella will help in the differentiating of patella fractures and avulsions from normal variants [ 2 ].…”
Section: Introductionmentioning
confidence: 99%